LANGUAGE ACQUISITION OF CHILDREN WITH MENTAL DISABILITIES IN PACITAN - Reza Pandudinata; Sumarlam Sumarlam; Kundharu Saddhono (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2018)
This research is a psycholinguistic research because it discusses about language acquisition. Focus of language acquisition will be discussed is language acquisition of child with severe mental disability, namely Angga, and a child with mild mental disability, namely Rafli. The purpose of this study is to explain the language acquisition of child with severe mental disability and a child with mild mental disability. This research is a qualitative research. The data of this research is basic vocabularies of child with severe mental disability and a child with mild mental disability. This research strategy is case study. This research was conducted at SLB YKK Pacitan. In this study, observation and questionnaires were used to collect the data. The results of this study were Angga, child with severe mental disability, understands 56 basic vocabularies of 200 basic vocabularies provided, while Rafli, a child with mild mental disability, was able to understand the 170 basic vocabularies. This is reasonable because the ability of child with severe mental disability and a child with mild mental disability has been very different. The child's "ability to understand" is reflected in the IQ of each child, if a child with mild mental disability rate ranges from 50-55 to 70, the child with severe mental disability ranges from 20-25 to 35-40, so the ability to understand this basic vocabularies is different.Keywords: psycholinguistic, language acquisition, children with mental disabilities PEMEROLEHAN BAHASA ANAK TUNAGRAHITA DI KABUPATEN PACITANAbstrakPenelitian ini merupakan penelitian psikolinguistik karena membahas salah satu objeknya, yaitu pemerolehan bahasa. Pemerolehan bahasa pada penelitian ini berfokus kepada pemerolehan bahasa anak tunagrahita berat, yaitu Angga, dan anak tunagrahita ringan, yaitu Rafli. Tujuan penelitian ini adalah memaparkan pemerolehan bahasa pada anak tunagrahita berat dan anak tunagrahita ringan. Penelitian ini merupakan penelitian kualitatif. Data yang diperoleh dari penelitian ini yaitu kosa kata dasar anak tunagrahita ringan dan anak tunagrahita berat. Strategi penelitian ini yaitu studi kasus. Penelitian ini dilaksanakan di SLB YKK Pacitan. Dalam penelitian ini, peneliti menggunakan metode observasi dan juga angket untuk mengumpulkan data. Hasil penelitian ini yaitu Angga, anak tunagrahita berat, mampu memahami 56 kosa kata dasar dari total 200 kosa kata dasar yang disediakan, sementara Rafli, anak tunagrahita ringan, mampu memahami 170 kosa kata dasar dari total 200 kosa kata dasar yang disediakan. Hal ini wajar karena memang kemampuan anak tunagrahita berat dan ringan tentu saja berbeda, khususnya di dalam berbahasa. “Kemampuan memahami” anak tergambar pada IQ masing-masing anak, jika IQ tunagrahita ringan berkisar antara 50-55 hingga 70, maka tunagrahita berat berkisar 20-25 hingga 35-40, sehingga kemampuan memahami kosa kata dasar ini Angga dan Rafli berbeda.Kata kunci: psikolinguistik, pemerolehan bahasa, anak tunagrahita